Position and attitude control of MAV quadrotor using super twisting sliding mode control - Noordin, Aminurrashid; Basri, Mohd Ariffanan Mohd; Mohamed, Zaharuddin; Lazim, Izzuddin Mat (2023)
This paper addresses the problem of robust actuated and under-actuated control of a Parrot Mambo Minidrone using Super Twisting Sliding Mode Control (STSMC). The dynamic model of the quadrotor was formulated using the Newtonian model by considering nonlinearity factor and perturbation. To test the robustness of the control method, this small-scale Micro Aerial Vehicle (MAV) was simulated without and with the presence of normal Gaussian white noise and pulse of force as external disturbances. The perturbations were assumed as excitation of 30% of the energy required for flight. Compared to classical Proportional-Integral-Derivative (PID) control, circle trajectory simulation results proved that the STSMC provides good performance and robustness against perturbation with less chattering input signal.